Helicobacter pylori Infection in Superficial Gastritis, Erosive Gastritis and Gastric Ulcer - Jacobus Albertus; Abdul Aziz Rani; Marcellus Simadibrata; Murdani Abdullah; Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
Background: Helicobacter pylori (H. pylori) infection leads to inflammation of the gastric mucosa. It damages the gastric epithelium and related to the risk of developing gastric cancer. Over time, it may develop into the development of glandular atrophy and intestinal metaplasia. This study was aimed to evaluate the histological features of gastric mucosa, including H. pylori infection in patients with endoscopically found superficial gastritis, erosive gastritis and gastric ulcer. Method: Subjects with abdominal complaints who underwent consecutive upper gastrointestinal endoscopy were prospectively selected at Tugurejo Hospital between November 2004 and December 2010. Eligible subjects were those with endoscopic diagnosis of superficial gastritis, erosive gastritis or gastric ulcer. The biopsy specimens were taken from the corpus, angulus and antrum of all the patients. Giemsa and hematoxylin-eosin staining were used for the histological diagnosis H. pylori and gastric mucosa inflammation. Results: The overall prevalence of H. pylori infection in superficial gastritis, erosive gastritis and gastric ulcer were 24.3%. There was significant difference between H. pylori infection rate in antrum of patients with superficial gastritis 19.4%, erosive gastritis 26.3%, and gastric ulcer 34.7%. The positivity rate of glandular atrophy and intestinal metaplasia of superficial gastritis with H. pylori- positivity was 12.5%, 14.0%; erosive gastritis 26.3%, 16.6%; and of gastric ulcer 38.9%, 29.3%; respectively. However, there was no significant difference. Conclusion: Patients with gastric ulcer have H. pylori infection, atrophic gastritis and metaplasia intestinal more than superficial gastritis and erosive gastritis. Progression of the gastric ulcer to atrophic gastritis and intestinal metaplasia is related to H. pylori infection. Keywords: Helicobacter pylori infection, superficial gastritis, erosion and ulcer